Refined GIS Mapping to Reinvestigate Groundwater Mining Potential Surrounding the Manmade Reservoirs and Tributaries in the Deduru Oya Basin, Sri Lanka - C. Jayasuriya, H.A.H. Jayasena (International Journal of Economic and Environment Geology, 2020)
A hydrogeologic study was carried out tounderstand the influence of Man-Made Reservoirs (MMR), tributariesand fractureintensity onwellyields within the Deduru Oya Basin(DOB),Sri Lanka. Anumber of cascadedMMRs interconnected by tributariesare distributed throughout the basin. Fracture traces, lineaments and reservoir boundaries were initially demarcatedusing aerial photographs, however, subsequently re-plotted them on to a Google Earth map with corrections to rectify the distortion. The GPS based well locationswere regenerated and plotted to obtain accurate dimensions. ArcGIS was used to redraw the buffer zones from 0-200, 200-400 and 400-600 m away from the MMRsand tributaries. After eliminating dry wells, box plots were prepared where lower and upper quartiles indicate yield variations from 18-470; 15.8-165 and 12.8–55 liters/minute respectively. It clearly exhibitsdecreasing yields with respect to distance away from the MMR. However, wells drilled withinthe alluvial plainsof tributariesafter filtering those controlledby the MMRs and eliminating dry wells indicate different yield variations,viz: 7-36.8; 12.8-67.5and6.5-142.5 liters/minute. The resultsassigned higheryieldsto the wells located away from the tributarieswith steep hydraulic gradientswhereas loweryields to the wells closerto the tributarieswith gentle hydraulic gradients. Moreover, wells drilled at fracture interconnections indicate a potential for high yieldscompared with those drilled along with a single fracture.The study concludes that the potential for groundwater mining can be enhanced by identifying high recharging areas such as MMRs,zones of steeper hydraulic gradients and high fracture interconnectivity